An empirical analysis on financial development and bilateral trade flow nexus. - UGLI, SHOMURODOV TOKHIR BOYMUROD; SADULLAYEVNA, KARIMOVA LATOFAT; QIZI, OHUNOVA OYGUL USMONJON; RASHIDOVNA, QUZIYEVA GULNOZA; UGLI, RAHMONOV BEKZOD SHARIBJON (The journal of contemporary issues in business and government, 2021)
This paper aims to analyze effect of the financial development level on bilateral trade flows of China and its trading partners, by the results are escorted with a panel data of 60 countries (china`s trading partners) under the period 2003-2017. The impact of financial development level on import and export flows of machine electronics, textile and machine transport products is estimated by employing random effects model, fixed effects model and Hausman-Taylor estimation methods. The results exhibit that China`s financial development has a negative effect on import flows, while it has positive and significant impact on exports of China. Additionally, it was found that financial development level of China`s trading partners is negatively correlated with textile exports of China. These results reveal that financial development level correlates differently with import and export flows.